Co-continuous structural electrolytes based on ionic liquid, epoxy resin and organoclay: Effects of organoclay content. (15th August 2016) - Yu, Yalin; Zhang, Boming; Wang, Yang; Qi, Guocheng; Tian, Fangyu; Yang, Jiping; Wang, Shubin
Abstract: As a vital part of structural power composites, structural electrolyte should achieve ionic conducting and load bearing functions simultaneously. In the present work, a novel method was established for optimizing the morphology and multifunctionality of a liquid/epoxy based structural electrolyte by adding different contents of organoclay (organically modified layered silicates, OLS). The OLS content had a substantial effect on the liquid/epoxy co-continuous morphology. The introduction of OLS changed the epoxy microstructure from the interconnected flakes to the parallel ridges. The increase of OLS content led to a more compact epoxy network and a more interpenetrated conductive phase. However, an excessive amount of OLS could cause the agglomeration and make the morphology parallel interconnected bars. The variation in morphology accounted for the multifunctionality increase in the structural electrolytes. The optimal formulation was determined with the best properties of 211 MPa in tensile modulus and 0.09 mS/cm in ionic conductivity, approaching the inferior limit of the multifunctional performance for a structural electrolyte. As a promising candidate for structural power composites, this co-continuous structural electrolyte containing ionic liquid, epoxy resin and OLS shows great potential to be used in the multifunctional energy storage devices. Graphical abstract: Highlights: Co-continuous structural electrolytes were prepared and investigated. Organoclay facilitates the formation of liquid/epoxy co-continuous morphology. Addition of organoclay contributes to a positive linear correlation between structural properties and ionic conductivity. The optimum organoclay content for multifunctional performance is 5 wt.%.